Geomagnetic disturbance intensity dependence on the universal timing of the storm peak. Issue 8 (12th August 2016) - Katus, R. M.; Liemohn, M. W.; Keesee, A. M.; Immel, T. J.; Ilie, R.; Welling, D. T.; Ganushkina, N. Yu.; Perlongo, N. J.; Ridley, A. J.
Abstract: The role of universal time (UT) dependence on storm time development has remained an unresolved question in geospace research. This study presents new insight into storm progression in terms of the UT of the storm peak. We present a superposed epoch analysis of solar wind drivers and geomagnetic index responses during magnetic storms, categorized as a function of UT of the storm peak, to investigate the dependency of storm intensity on UT. Storms with Dst minimum less than −100 nT were identified in the 1970–2012 era (305 events), covering four solar cycles. The storms were classified into six groups based on the UT of the minimum Dst (40 to 61 events per bin) then each grouping was superposed on a timeline that aligns the time of the minimum Dst . Fifteen different quantities were considered: seven solar wind parameters and eight activity indices derived from ground‐based magnetometer data. Statistical analyses of the superposed means against each other (between the different UT groupings) were conducted to determine the mathematical significance of similarities and differences in the time series plots. It was found that the solar wind parameters have no significant difference between the UT groupings, as expected. The geomagnetic activity indices, however, all show statistically significant differences with UT during the main phase and/or early recovery phase. Specifically, the 02:00 UT groupings are stronger storms than those in the other UT bins. That is, storms are stronger when the Asian sector is on the nightside (American sector on the dayside) during the main phase. Key Points: We statistically examine storm time solar wind and geophysical data as a function of UT of the storm peak There is a significant UT dependence to large storms; larger storms occur with a peak near 02:00 UT The difference in storm magnitude is caused by substorm activity and not by solar wind driving